Less Known Ethnomedicinal Plants Used by Kurichar Tribe of Wayanad District, Southern Western Ghats Kerala, India - Binu Thomas and A. Rajendran (Botany Research International, 2013)
The present study provides an over view of 44 medicinal plants belonging to 30 families have been used for indigenous medication by the tribe Kurichar of Wayanad district of Kerala. Among them Asclepiadaceae, Fabaceae, Acanthaceae, Rutaceae, Apocynaceae, Marantaceae, Rubiaceae and Solanaceae are the most common plant families, respectively. The different parts of plants of these famililies are used to cure various ailments like stomach problems, urinary complaints, rheumatism, leprosy, eye diseases, bronchitis, malaria, diabetes, chicken pox, cough and cold, head ache, hair tonic, cuts and wounds, skin problems etc. The botanical, vernacular and family names along with mode of preparation and uses have been provided for further pharmacological and clinical evaluations.